CircSMARCA5: A key circular RNA in various human diseases - Zhu, Yi; Huang, Gaozhen; Li, Shihao; Xiong, Hong; Chen, Ruiqi; Zuo, Ling; Liu, Hongwei (Frontiers in Genetics, 2022)
Circular RNAs (circRNAs) are recognized as a novel type of single-stranded endogenous noncoding RNA molecule with the characteristics of tissue specificity, sequence conservation and structural stability. Accumulating studies have shown that circRNAs play a unique biological role in different kinds of diseases. CircRNAs can affect tumor proliferation, migration, metastasis and other behaviors by modulating the expression of downstream genes. CircSMARCA5, an example of a circRNA, is dysregulated in various noninfectious diseases, such as tumors, osteoporosis, atherosclerosis and coronary heart disease. Furthermore, recent studies have demonstrated that circSMARCA5 is associated with the occurrence and development of a variety of tumors, including gastric cancer, glioblastoma, hepatocellular carcinoma, multiple myeloma, colorectal cancer, breast cancer and osteosarcoma. Mechanistically, circSMARCA5 primarily acts as a sponge of miRNAs to regulate the expression of downstream genes, and can serve as a potential biomarker for the diagnosis of malignant tumors. This review summarizes the biological roles of circSMARCA5 and its molecular mechanism of action in various diseases. Moreover, the meta-analysis of some publications showed that the expression of circSMARCA5 was significantly correlated with the prognosis of patients and tumor TNM stage, showing that circSMARCA5 has the potential to be a prognostic marker.